2012
DOI: 10.1007/s11033-012-2357-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of LRP5 haplotypes with osteoporosis in Mexican women

Abstract: Osteoporosis is a common health problem in Mexico, so it is essential to investigate the status of different gene polymorphisms that could serve as genetic susceptibility markers in the Mexican population. Genes with a role in bone metabolism are excellent candidates for association studies. In this study were determined the allelic and genotypic frequencies of four polymorphic markers (C/T rs3736228, G/A rs4988321, T/C rs627174 and T/C rs901824) in the low-density lipoprotein receptor-related protein 5 gene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…However, although the nonsynonymous rs3736228 in LRP5 and rs2302685 in LRP6 are the most frequently studied SNPs in candidate gene studies Tran et al 2008;Lee et al 2009), they were not associated with BMD in Mexican women. This lack of association is in accordance with the report of Falcón-Ramírez et al (2013), who analyzed rs3736228, rs4988321, rs627174, and rs901824 in the LRP5 gene in a small case-control study of unrelated Mexican women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although the nonsynonymous rs3736228 in LRP5 and rs2302685 in LRP6 are the most frequently studied SNPs in candidate gene studies Tran et al 2008;Lee et al 2009), they were not associated with BMD in Mexican women. This lack of association is in accordance with the report of Falcón-Ramírez et al (2013), who analyzed rs3736228, rs4988321, rs627174, and rs901824 in the LRP5 gene in a small case-control study of unrelated Mexican women.…”
Section: Discussionsupporting
confidence: 90%
“…In the Mexican population, specific genetic factors of BMD variation remain largely unknown as only a few candidate gene studies have been reported in reduced samples and/or analyzing few SNPs (Lisker et al 2003;Gómez et al 2007;Magaña et al 2008;Falcón-Ramírez et al 2011;Rojano-Mejía et al 2013;Falcón-Ramírez et al 2013). The aim of the present study was to seek associations of Wnt pathway gene variants with BMD at various skeletal sites in Mexican mestizo postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…This led them to conclude that this SNP has a significant association with osteoporosis in this population. An equally interesting finding was that when the authors analyzed the haplotypes of these polymorphisms, there was a clear association between osteoporosis in two haplotypes: the CGTT haplotype was related with lower risk of osteoporosis; and the TACT haplotype was significantly associated with higher risk of osteoporosis [57]. …”
Section: Lrp Mutations In Bone Related Diseasesmentioning
confidence: 99%
“…LRP5 encodes a transmembrane protein in the WNT signaling pathway and regulates bone mass in humans and mice [40]. Several studies have shown that LRP5 polymorphisms are a determining factor of bone mass [41]. In this study, we rst found that rs2291467, rs11228240 and rs12272917 of LRP5 were signi cantly associated with a decreased risk of osteoporosis and that the relationships were BMI-dependent.…”
Section: Discussionmentioning
confidence: 62%